Sepaktakraw Players Injuries Event - Astry Khairunnisa; Pipit Pitriani (JUARA : Jurnal Olahraga, 2020)
Sepaktakraw basically requires acrobatic skills (ex: backflip, sunback spike, split, etc) that has high difficulty in playing it. The aim of this study was to look the incident of injuries (injury body parts, type of injury, and mechanism of injury). This study used descriptive research methods. 40 male and female athletes participated in the pre-season for Indonesian national competition (PON) 2020. The instruments used were questionnaires and interviews regarding the injury body parts, types of injuries and mechanisms injury. The results showed that the most damage experienced by sepaktakraw players occurred at the ankle (27%) with the type of sprained injury (47.5%) and was most widely known by server-positioned players and killer/spiker compilation when they did serve movements (27%) and spike (30%).